2019
DOI: 10.2903/sp.efsa.2019.en-1674
|View full text |Cite
|
Sign up to set email alerts
|

ENETwild modelling of wild boar distribution and abundance: update of occurrence and hunting data‐based models

Abstract: In October 2018 the ENETWILD consortium created suitability maps based on available data on wild boar occurrence at 10 km square resolution and initial version of abundance models based on hunting statistics at NUTS3 and NUTS2 resolution, that were statistically downscaled for MSs to 10x10 km grid squares. This report presents updated suitability map for wild boar presence based on additional occurrence data and new algorithms, and new models based on highresolution hunting yield data for MSs and neighbouring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…The model identified a rate of spread of ASF of ∼4 km/month within the core population at densities around 15 boar/km 2 , reducing to nearer 2 km/month toward the population edge where densities were closer to that observed in Europe (5 boar/km 2 ). This compares well with an empirical description of 1.5 ± 1.3 km/month for the same disease in boar in Poland (27), 1-2 km/month in a number of eastern European countries (24), and a broader range of estimates for the unassisted spread of ASF cited in (7) between 8 and 25 km/year, though most fall between 10 and 17 km/year (0.8-1.4 km/month). Whilst not a definitive validation of our model, the similarity of our result with that of others suggests that our representation and parameterization of our model system is of some value and is free of substantial consistent bias.…”
Section: Model Validationsupporting
confidence: 88%
“…The model identified a rate of spread of ASF of ∼4 km/month within the core population at densities around 15 boar/km 2 , reducing to nearer 2 km/month toward the population edge where densities were closer to that observed in Europe (5 boar/km 2 ). This compares well with an empirical description of 1.5 ± 1.3 km/month for the same disease in boar in Poland (27), 1-2 km/month in a number of eastern European countries (24), and a broader range of estimates for the unassisted spread of ASF cited in (7) between 8 and 25 km/year, though most fall between 10 and 17 km/year (0.8-1.4 km/month). Whilst not a definitive validation of our model, the similarity of our result with that of others suggests that our representation and parameterization of our model system is of some value and is free of substantial consistent bias.…”
Section: Model Validationsupporting
confidence: 88%
“…In Europe, TB prevalence in wild boar varied between 31.68% in Spain and 9.49% in France, with Italy (23.84%), Hungary (18.12%) and Portugal (13.03%) also being remarkably affected. All studied European countries showed higher estimated TB prevalence values, with the South bioregion that is comprised by Portugal, Spain and Italy, and where the estimation of wild boar density is higher (Enetwild consortium et al, 2019), also showed higher estimates of animal TB prevalence. Similar to the European badger model, larger sample sizes (>250) were associated with lower prevalence numbers, probably related to a more accurate assessment of estimated disease prevalence.…”
Section: Wild Boar (Sus Scrofa)mentioning
confidence: 88%
“…Today, in addition to direct observations, the majority of European countries (64 %) uses hunting bag statistics as a proxy for assessing relative changes in the distribution and abundance of ungulates at national scales (Apollonio et al 2010;Putman et al 2011). Following the need of crossborder management (Linnell et al 2020), recent initiatives develop abundance models using hunting statistics at the European scale (ENETWILD-consortium et al 2019). Hunting bags, however, may not be reliable if the hunting effort of a species is not related to its density and when this relationship changes over time (Imperio et al 2010;Willebrand et al 2011;Ferretti et al 2016;Eriksen et al 2018).…”
Section: Introductionmentioning
confidence: 99%